KENDALA PENERAPAN PRINSIP CABOTAGE DALAM RANGKA TERLAKSANANYA ASEAN OPEN SKY - R. Rizky Aulia (BELLI AC PACIS, 2020)
This research aims to understand and analyze the constraints of applying the cabotage principle conducted by Indonesia in the framework of ASEAN open sky. This research is a normative legal research that is descriptive analysis. The type of data used is secondary data that includes primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques using library study methods, while data analysis techniques use legal interpretation. The results of this legal research show that with the concept of open sky that apply impact in its implementation in applying the cabotage principle by Indonesia that raises problems both internally and technically as Infrastructure, water traffic management, regulatory readiness and also technical operations in the field. The advice that can be given is that the government needs to quickly arrange, establish, and implement a national administrative governance in order to create a clear standardization of the airport.